PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Ruteng) - Win Susilo Hari Endrias (Universitas Mercu Buana, 2014)
Abstract: The purpose of this research is to investigate the effects of leadership style and corporate culture on job satisfaction to enhance employee performance. Exogenous variables in this study is the style of leadership, corporate culture toward job satisfaction as an intervening variable to increase employee’s performance as endogenous variable. The study was conducted at Ruteng small tax office, the sample size is about 49 employee, using the Structural Equation Modelling (SEM) with PartialLeast Square (PLS). The results showed that corporate culture has positive significance effect on job satisfaction and increase employee performance. The effect of leadership style on job satisfaction is positive significant, but negative significant to increase employee performance. The conclusion of this study, in order to increase performance of employees, companies must be able to provide leadership style that is personal attention to employee, corporate culture that can be applied in the form of synergybetween employee and expected job satisfaction is satisfaction with the work itselfKeywords: leadership style, corporate culture, job satisfaction, employee performance